Mechanisms of anti-nutritional factor degradation and quality enhancement in soybean meal via Rpf-mediated microbiota synergy and Bacillus reinforcement during solid-state fermentation - Zhang, Yujia; Xie, Yuxiao; Ma, Jun; Hu, Dong; Zhang, Xiumin (Frontiers in Animal Science, 2025)
As the core protein source in livestock and poultry feed, soybean meal has its nutritional value limited by anti-nutritional factors (ANFs). This study innovatively combined the Resuscitation Promoting Factor (Rpf) of Micrococcus luteus with Bacillus velezensis and B. amyloliquefaciens in a solid-state fermentation. The aim was to activate functional microbial communities within the system, enabling synergistic degradation of ANFs and improve the nutritional quality of soybean meal. Results demonstrated that the Rpf-treated group significantly accelerated the degradation of glycinin, β-conglycinin, and trypsin inhibitor (the degradation efficiency within 48 hours was 1.28-2.0 times of the control group), while enhancing the enzyme activities of acid protease, amylase, and cellulase. Microbial diversity analysis revealed that Rpf promoted the proliferation of Bacillota by 18.91 percentage points and concurrently suppressed potential pathogenic bacteria, reducing their genus diversity from 8 to 3 and their cumulative relative abundance from 18.5% to 4.88%. Metabolomics profiling indicated that the Rpf-treated group upregulated key metabolites, including phospholipids, amino acids (e.g., serine and arginine), and vitamins. This was accompanied by enhanced glycerophospholipid metabolism and isoflavone biosynthesis pathways, which collectively improved the antioxidant and antibacterial properties of soybean meal. The study confirms that Rpf optimizes the fermentation system through the “functional bacterial resuscitation-Bacillus synergy” mechanism, providing a theoretical foundation and technical strategy for efficient soybean meal biotransformation and feed quality enhancement.